2005
DOI: 10.1002/glia.20179
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of GFAP, TSP‐1, and p53 in human glioblastoma cell line, U373MG, by IE1 protein from human cytomegalovirus

Abstract: Human cytomegalovirus (HCMV) is a member of the b-herpesvirus family, which has tropism for glial cells. It was recently reported that HCMV might play important roles in the pathogenesis of malignant glioma. In this study, we investigated the effects of the HCMV IE1 protein on the gene expression profile in the human glioblastoma cell line, U373MG by employing cDNA microarray technology. Using DNA chips containing approximately 1,000 human cDNAs, RNA samples from U373MG cells stably expressing IE1 were compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
32
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 67 publications
5
32
0
Order By: Relevance
“…In the present study, hTERT was cloned together with the E1A gene into pGL3-Basic to induce E1A expression in tumor cells. GFAP, which was used in the present study as a promoter, has been previously demonstrated to be able to promote p53 expression and is downregulated in glioblastoma cells (20,21). GFAP and hTERT have been demonstrated to be glioma specific and are not expressed in MRC-5 cells (11), and these findings were confirmed in the present study.…”
Section: Discussionsupporting
confidence: 84%
“…In the present study, hTERT was cloned together with the E1A gene into pGL3-Basic to induce E1A expression in tumor cells. GFAP, which was used in the present study as a promoter, has been previously demonstrated to be able to promote p53 expression and is downregulated in glioblastoma cells (20,21). GFAP and hTERT have been demonstrated to be glioma specific and are not expressed in MRC-5 cells (11), and these findings were confirmed in the present study.…”
Section: Discussionsupporting
confidence: 84%
“…HCMV IE1-72 and IE2-86 were knocked down in HEL cells after HCMV infection by small interfering RNAs (siRNAs) as described previously (41,80). In brief, the IE1-72 siRNA 5ЈGGU UAUCAGUGUAAUGAAGdTdT-3Ј and complement 5ЈCUUCAUUACACU GAUAACCdTdT-3Ј targeting HCMV IE1-72 as well as the IE2-86 siRNA oligonucleotide 5Ј-AAACGCAUCUCCGAGUUGGACdTdT-3Ј and complement 5Ј-GUCCAACUUGGAGAUGCGUUUdTdT-3Ј targeting HCMV IE2-86 were synthesized by Dharmacon (Lafayette, CO) as described previously (74).…”
Section: Methodsmentioning
confidence: 99%
“…Many data have indicated that both IE1 and IE2 stimulate transcription from a variety of cellular and viral genes involved in viral replication and cell survival, alone or in concert with other transcriptional regulators, including the Rb family members, the E2F family members, p53, SP1, TAFII130/TAF4 and histone modification proteins (Bonin & McDougall, 1997; Bryant et al, 2000;Fortunato et al, 1997;Hayhurst et al, 1995;Lukac et al, 1997;Margolis et al, 1995;Nevels et al, 2004b;Pajovic et al, 1997;Poma et al, 1996;Schwartz et al, 1996). The interplay between the IE proteins of HCMV and cellular factors has been implicated in disrupting normal cell-cycle progression and impeding apoptosis (Castillo Lukac & Alwine, 1999;Murphy et al, 2000;Song & Stinski, 2002;Tanaka et al, 1999;Yu & Alwine, 2002;Zhu et al, 1995).We reported previously that the IE1 protein could modulate the expression of various cellular genes, including those implicated in carcinogenesis, in the human glioblastoma cell line U373MG (Lee et al, 2005). The gene most affected by IE1 was glial fibrillary acidic protein (GFAP), an intermediate filament protein that has been widely used as a marker for cells of astroglial lineage under pathological as well as normal conditions (de Armond et al, 1980;Deck et al, 1978).…”
mentioning
confidence: 86%